Wound healing in diabetic rats: Comparative efficacy of topical Insulin, Jatyadi formulations and Silver sulphadiazine” - Vijay Haribhau Mate; Priti P. Dhande; Vijaya A Pandit; Hardik R Patel; Siddharth M Hardikar (International Journal of Phytomedicine, 2014)
To compare the effect of topical insulin, silver sulfadiazine and two ayurvedic formulations (jatyadi-ghrita and jatyadi-tail) on excision wound in experimentally induced diabetic rats. Diabetes Mellitus was induced by single intraperitoneal (i.p.) injection of 150mg/kg alloxan in wistar rats weighing 150-200gm.Study animals were divided into 6 groups of six rats each.Group I- Non Diabetic Control (no treatment), Group II - Diabetic Control (no treatment), Group III – Topical Insulin, Group IV – Silver Sulpfadaizine, Group - V Jatyadi-tail and Group VI- Jatyadi-Ghrita.An excision wound was inflicted in all rats by cutting full thickness of a pre-determined area (1 X 1 cm) on the depilated back of the rat under ether anesthesia. Drug treatment was given topically once daily. The healing was assessed by parameters like epithelialization period and wound contraction. The results were analyzed using One-way ANOVA followed by Tukey’s test by SPSS Software Version 20. Epithelization was delayed in diabetic control animals(18 days) in comparison to non diabetic control animals(12 days) and was hastened in all drug treated groups (insulin-8 days; silver sulfadiazine-10 days; jatyadi tail-11days and jatyadi ghrita-15 days) in comparison to diabetic control animals. There was significant improvement in wound contraction in Groups III-V (p<0.05from day 8 onwards) as compared to diabetic control group. Topical insulin has comparable wound healing efficacy to silver sulfadiazine in alloxan induced diabetic rats.Jatyadi tail also has shown very promising results in this model.